Clinical diagnosis and treatment of throat foreign bodies under video laryngoscopy. Issue 7 (July 2020) - Lin, Chuanyao; Liu, Dingding; Zhou, Han; Zhang, Xiaoli; Lu, Ling; Gao, Xia
Objective: This study was designed to explore the clinical application of video laryngoscopy in the diagnosis and treatment of throat foreign bodies (FBs). Method: In total, 1572 patients diagnosed with throat FBs at the Department of Otolaryngology of Nanjing Drum Tower Hospital were retrospectively analysed. The covariables collected were the time from FB ingestion to admission, age, sex, duration of admission, and site of impaction. Result: The most common FBs were fish bones, which accounted for 1446 (91.98%) of 1572 FBs. Among all 1572 FBs, 1004 (63.87%) were successfully removed by video laryngoscopy without complications. A shorter duration of admission was associated with a higher diagnostic rate under video laryngoscopy. The diagnostic rate of sharp FBs was significantly higher than that of non-sharp FBs. The most common sites of throat FBs were the tongue root (42.29%), epiglottic vallecula (19.40%), tonsil (18.21%), and piriform fossa (10.65%). Conclusion: Video laryngoscopy is a powerful tool for the diagnosis and treatment of throat FBs, allowing for identification of rare locations of FBs as well as refractory FBs.